2013
DOI: 10.1002/nbm.2992
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative MRI and ultrastructural examination of the cuprizone mouse model of demyelination

Abstract: The cuprizone mouse model of demyelination was used to investigate the influence that white matter changes have on different magnetic resonance imaging results. In vivo T2 -weighted and magnetization transfer images (MTIs) were acquired weekly in control (n = 5) and cuprizone-fed (n = 5) mice, with significant increases in signal intensity in T2 -weighted images (p < 0.001) and lower magnetization transfer ratio (p < 0.001) in the corpus callosum of the cuprizone-fed mice starting at 3 weeks and peaking at 4 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
167
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(199 citation statements)
references
References 91 publications
(215 reference statements)
27
167
5
Order By: Relevance
“…We opted to investigate the well-established CPZ mouse model for MS, whose strengths lie in the localization of the lesions, their well-known pathogenesis, and their reproducibility in time and space, allowing for longitudinal validation of imaging methods (37,47,48). In this model, the vast majority of activated MPs are endogenous microglia, not peripheral macrophages (49)(50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%
“…We opted to investigate the well-established CPZ mouse model for MS, whose strengths lie in the localization of the lesions, their well-known pathogenesis, and their reproducibility in time and space, allowing for longitudinal validation of imaging methods (37,47,48). In this model, the vast majority of activated MPs are endogenous microglia, not peripheral macrophages (49)(50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%
“…Practical interest in MPF as a prospective biomarker in MS is driven by a number of recent animal studies (4,5,(12)(13)(14)(15)(16) that demonstrated strong relationships between MPF and myelin. MPF has been highly positively correlated with histologic measurements of myelin density in animal models, including both normal brain tissues and demyelination (4,12,15,16).…”
mentioning
confidence: 99%
“…MPF has been highly positively correlated with histologic measurements of myelin density in animal models, including both normal brain tissues and demyelination (4,12,15,16). Based on quantitative estimates from the literature (5), myelin provides an at least 75% contribution into the MPF measured in white matter (WM).…”
mentioning
confidence: 99%
“…On the other hand, some believe myelin does not play a large role in restricting diffusion and thus demyelination will not affect DTI (5)(6)(7)(8).…”
Section: Comparison Of Tractography In Mouse Modelsmentioning
confidence: 99%